IN VIVO TEST OF ANTIMALARIAL ACTIVITY FROM DICHLOROMETHANE-ETHYL ACETATE-METHANOL FRACTIONS OF MUNDU’S BARK(GARCINIA DULCIS (ROXB.) IN SWISS WEBSTER MICE - Rahayu, Mamik Ponco; Harmastuti, Nuraini; Pamudji, Gunawan; R, Dimas Klodengan; Supargiyono, Supargiyono; Wijayant, Mahardika Agus (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Genus Garcinia is well-known having rich xanthone compound contents and several of those are having biological activity as antimalarial. The aims of this research wereto determine in vivoantiplasmodialactivityof dichloromethane-ethyl acetate-methanol fractions of Mundu’s bark (Garciniadulcis (Roxb.) Kurz) especially fraction Vagainst Plasmodium bergheiand to determineeffective dose. Methods: Making fraction V from ethyl acetate extractsof Mundu’s bark with vacuum column chromatographymethod was applied using dichloromethane-ethyl acetate-methanol. The product was monitored by thin layer chromatography using silica gel GF-254 and a mobile phase of chloroform: ethyl acetate (6:4).The same profiles from eluent composed fraction 18 and 19 were categorized as fraction V.Those were tested in each of groups animals with a doseof 12.5; 25; 50 and 100 mg/kg body weight. Antimalarial activityassessments have been performed with the in vivoPlasmodium bergheitest. Plasmodial activity was obtained by calculating percentage of parasitaemia, parasitaemia inhibition and ED50 determination. ED50value determined based on the relationship between dose and the percentage of parasite growth inhibition by probit analysis. Results: In this research, Antiplasmodial activity of fraction V from Mundu’s bark displayed in dose of 50 mg/kg bw and 100 mg/kg bw with inhibition parasite growth by values of 47.255% and 12.761%, respectively. Conclusion: According to the research, fraction V of Mundu’s bark (Garcinia dulcis (Roxb.) Kurz) had the most potential antiplasmodial activity by in vivo test for male Swiss-Webster mice. The value of ED50 was reached by 47.424 mg/kg bw. Â Keywords: Mundu’s bark, Antiplasmodial activity, ED50.